Adapting Helping Babies Breathe into a Virtual Curriculum: Methods, Results, and Lessons Learned - Celia Sobelman MD; Kristen Richard MD; Patricia McQuilkin MD; Nisha Fahey DO (SAGE Publishing, 2021)
Introduction . The Helping Babies Breathe (HBB) curriculum is an established, effective method to combat neonatal mortality. The COVID-19 pandemic has disrupted in-person HBB training sessions worldwide, portending deficits in the dissemination of this important intervention. Methods . A pilot study to compare in-person versus virtual HBB training among US-based pediatric and family medicine residents. Two HBB master trainers condensed the curriculum into an abbreviated course that was offered to 14 learners in-person (n = 6) and virtually via Zoom (n = 8). A standardized 10-item survey was administered before and after the session to measure reported self-efficacy of critical elements of HBB. Difference of difference analysis was performed to detect differences in post vs pre-training results among the 2 groups using STATA MP 15. Results . All learners showed improvement in preparedness, assessment, and skills subcomponents of self-efficacy with no notable differences based on the type of learning medium. At baseline, in-person learners had a 7-point higher self-efficacy score (69.7) in comparison to virtual learners (62.8; P  = .26). After training, the confidence score improved significantly; by 14.3 units for in-person learners ( P  = .01) and 12.9 for virtual learners ( P  = .04). There was no statistically significant difference in improvement between the 2 groups ( P  = .67). Furthermore, all learners passed the post-training knowledge assessment. Discussion . Virtual learning of HBB may be an alternative option in the setting of resource and travel limitations. Future work needs to assess possible differences in attainment of assessment skills and retention of the HBB curriculum among virtual learners.